The potential impact of new diagnostic tests on tuberculosis epidemics - Dye, Christopher (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND & OBJECTIVES: New diagnostic tests for tuberculosis, especially those based on nucleic acid amplification, offer the possibility of early and accurate diagnosis of active TB. In this study we use mathematical modelling to explore the potential epidemiological impact of these new tests, with particular reference to India. METHODS: A behavioural model of patient-doctor interactions embedded in an epidemiological model of Mycobacterium tuberculosis transmission, linked to field data, was used to investigate the effects of early diagnosis in preventing future TB cases. RESULTS: New diagnostic tests for active TB will have a bigger impact sooner where: disease incidence is high and most cases are due to recent infection; advances in test technology (test sensitivity, specificity, etc.) are combined with early diagnosis; new tests have not only better technical specifications than current tests, but also compensate for the misuse of existing tests; health system delays are long compared with patient delays, assuming the former are more amenable to change. INTERPRETATION & CONCLUSIONS: New diagnostic tests will certainly improve TB control, but the highest impact will be obtained by applying tests with higher sensitivity and specificity early in the infectious period. Refined behavioural and epidemiological models should be able to investigate the mechanisms by which early diagnosis could be achieved, in addition to the consequent epidemiological effects.